A framework for hybrid simulation of transportation networks. Issue 2 (4th March 2022) - Gomes, Gabriel
ABSTRACT: This paper introduces a new approach to hybrid traffic modelling, along with its implementation in software. The software allows modellers to assign traffic models to individual links in a network. Each model is a plugin that implements a series of methods, referred to as the modelling interface. These methods are used by the program to exchange information between adjacent models. Traffic controllers are implemented in a similar manner. The paper outlines the important components of the method: the network description, the description of demands, and the modelling and control interfaces. We include tests demonstrating the propagation of congestion between pairs of macroscopic, mesoscopic, and microscopic models. Open Traffic Models is an open-source implementation of these concepts, and is available at https://github.com/ggomes/otm-sim .